An evaluation of the effects of handpiece speed, abrasive characteristics, and polishing load on the flexural strength of polished ceramics - Ahmad, Rohana; Morgano, Steven M.; Wu, Benjamin M.; Giordano, Russell A. (Elsevier, 2005)
Statement of problem. Many studies on the strengthening effects of grinding and polishing, as well as heat treatment on ceramics, are not well standardized or use commercially available industrial polishing systems. The reported effectiveness of these strengthening mechanisms on ceramics may not be applicable to clinical dentistry. Purpose. The purpose of this study was to evaluate the effects of controlled polishing on the flexural strength of dental ceramics by using a custom-made machine that applied standardized loads and speeds that coincided with the mean loads and speeds used by experienced prosthodontists. Material and methods. A total of 140 aluminous dental ceramic bar-shaped specimens (Vitadur Alpha Enamel) measuring 1.5 x 2.0 x 25 mm were fabricated and divided into 12 groups (for most groups, n=10). Specimens were untreated, polished with different polishing systems, polished at different speeds, ground and autoglazed, polished and autoglazed, autoglazed and polished, polished with loose (paste) and bonded abrasives, or overglazed. Simulated clinical polishing was performed on the ceramic specimens by using a customized polishing apparatus that allowed independent control over the relevant polishing parameters (abrasive hardness, applied load, linear speed, rotational velocity, and wheel stiffness). Flexural strength (MPa) was measured with a 4-point bending test, and subjective surface roughness was assessed with scanning electron microscopy. Autoglazing was performed at various stages of the polishing sequence to determine the effects of polishing on surface stresses. Mean values, standard deviations, independent-sample t tests, 1-way and 2-way analyses of variance, Dunnett t tests and Kruskal-Wallis tests were applied to the data (α=.05). Results. Under a clinical load of 0.6 N for a coarse polishing wheel, 1.0 N for a medium polishing wheel, and 1.3 N for a fine polishing wheel, a linear speed of 499 mm/min, and a rotational velocity of 10,000 rpm, the use of clinical polishing instruments did not affect the flexural strength of the aluminous ceramics studied (P=.274). At higher rotational velocity (20,000 rpm), specimens polished with the diamond polishing system produced statistically weaker specimens compared with those that had been polished at 10,000 rpm (P=.019). Autoglazing treatment of the diamond-polished specimens did not reverse the strength degradation (P=.125). Conversely, diamond polishing of the autoglazed specimens resulted in significant flexural strength reduction (P=.029). Fine-diamond-bonded abrasive significantly reduced flexural strength (P=.025). Conclusions. Simulated clinical polishing at 10,000 rpm did not appear to substantially strengthen or weaken the ceramic specimens. Polishing at 20,000 rpm reduced flexural strength of the ceramic bars. Copyright © 2005 by The Editorial Council of The Journal of Prosthetic Dentistry.